A Computational Algorithm for Multi-Contract Bidding Under Constraints - Goodman, David; Baurmeister, Hans (Management Science, 1976)
This paper considers a multi-contract bidding situation in which the contracts are interrelated because of limited productive facilities and because of budgetary constraints. A dynamic programming model and computational algorithm are presented which derive a bidding strategy which maximizes total expected return from all contracts subject to the constraints. The computational algorithm is efficient in terms of storage capacity required and computation time.